Biomarkers of inflammation and multisystem tissue and organ damage in patients with COVID-19 - Arsenijevic, Jana; Milovanovic, Dragan; Jankovic, Slobodan; Jovanovic, Danijela; Djordjevic, Jelena; Mijailovic, Sara; Matic, Andjela; Jevtic, Mirela; Gencic, Milena; Jurisic, Vladimir; Mihaljevic, Olgica; Stanojević Pirković, Marijana (Medicinski časopis, 2025)
Objective. The importance of in vitro laboratory diagnostic tests for COVID-19 lies in assessing disease severity, monitoring patients, therapeutic monitoring, and predicting disease prognosis. The aim of our study was to evaluate inflammation biomarkers in COVID-19 patients and their association with biomarkers of cardiomyocyte, liver, and kidney damage, and how they impact disease progression.                                        Methods. The study included 50 patients, 38 (76%) male and 12 (24%) female, with an average age of 64.38 ± 10.95 years, treated for COVID-19 in 2021 at the Clinic for Infectious Diseases of the University Clinical Center Kragujevac. Biomarkers of inflammation, cardiomyocyte, liver, and kidney damage were analyzed at the beginning of hospitalization and on the tenth day using standard laboratory methods and autoanalyzers. Results. Analysis showed a significant increase in inflammation parameters on the tenth day of hospitalization compared to initial values: leukocytes (p=0.003), neutrophils (p=0.002), platelets (p
Keywords: biomarkers, COVID 19, inflammation, multisystem damage